Validation of High-Throughput Sequencing as Virus Indexing Test for Musa Germplasm: Performance Criteria Evaluation and Contamination Monitoring Using an Alien Control - Wei Rong; Johan Rollin; Marwa Hanafi; Nicolas Roux; Sebastien Massart (PhytoFrontiers, 2023)
High-throughput sequencing (HTS) technologies have brought tremendous improvements in the ability to detect plant viruses and have great potential for application in virus routine diagnostics. The performance criteria of an HTS test need therefore to be estimated and compared with traditional virus indexing tests before it can be used in routine diagnostics. In this study, 78 Musa accessions previously indexed for viruses by molecular tests and/or electron microscopy were tested individually or in pools using an HTS protocol based on total RNA sequencing. The analytical sensitivity of HTS and RT-PCR was also compared by independent testing on serial dilutions of RNA extracts. In total, 136 libraries were sequenced in five batches, and the sequences were analyzed for virus detection. The external alien control, a wheat sample infected by barley yellow dwarf virus, monitored the contamination burden and determined an adaptative detection threshold. Overall, the HTS test displayed a better analytical sensitivity than the RT-PCR and a better inclusivity than the classical indexing protocol, as distant isolates and new viral species were only detected by the HTS test. The repeatability and reproducibility of virus detection were both 100%, although differences in number of sequencing reads per virus were observed between replicates. The diagnostic sensitivity was very high, but false positive results were observed. Finally, the results also underlined the need for expert judgement in the interpretation of the results. In conclusion, the HTS test with an alien control and completed by expert evaluation fulfilled the criteria of the virus indexing protocol for Musa germplasm. [Figure: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.